Research of Lightning Protection Systems of Wind Power Plant - Potapenko A.N.; Kumar Udaya; Shtifanov A.I.; Soldatenkov A.S. (Problems of the Regional Energetics, 2019)
The work is dedicated to the study of the influence of the wind turbine lightning protection system on the possibility of a lightning strike to the lightning rod, to the protected object and to the surface of the earth. The aim of the work is to study atmospheric electric fields for a complex object: a wind turbine, a thundercloud and a surface of the earth, in two versions - with and without a lightning protection system. This goal is achieved by constructing a mathematical model based on the Laplace equation of elliptic type and boundary conditions for calculating the electric flow function. Computational experiments over a wind turbine carried out in two basic configurations: using a rod-type lightning protection system and without it. The most significant result of the work is a mathematical model with boundary conditions that determines the rigid boundaries of the object of study and constant values at the free and symmetric boundaries for calculating the electric flow function, the method of finding the specific distribution of the lines of the flow function along the boundaries of the studied wind power installation, and the results of computational experiments. As a result, it was found that the applied numerical calculation method allows analyzing the features of the atmospheric electrostatic field near the pointed peaks. The proposed mathematical model makes it possible increasing of the efficiency of lightning protection of a power plant and can be used to simulate other objects using a rod type of lightning protection.